Health and social care services for older male adults in prison: the identification of current service provision and piloting of an assessment and care planning model - J Senior; K Forsyth; E Walsh; K O'Hara; C Stevenson; A Hayes; V Short; R Webb; D Challis; S Fazel; A Burns; J Shaw (National Institute for Health Research, 2013)
Background: Older prisoners are the fastest growing subgroup in the English and Welsh prison estate. Existing research highlights that older prisoners have high health and social care needs and that, currently, these needs routinely remain unmet. Objectives: (1) To explore the needs of men entering and leaving prison; (2) to describe current provision of services, including integration between health and social care services; and (3) to develop and pilot an intervention for identifying health and social care needs on reception into prison, ensuring that these are systematically addressed during custody. Methods: The research programme was a mixed-methods study comprising four parts: (1) a study of all prisons in England and Wales housing older adult men, establishing current availability and degree of integration between health and social care services through a national survey and qualitative interviews; (2) establishing the health and social care needs of older men entering prison, including experiences of reception into custody, through structured (n = 100) and semistructured (n = 27) interviews; (3) the development and implementation of an intervention to identify and manage the health, social care and custodial needs of older men entering prison; and (4) exploration of the health and social care needs of older men released from prison into the community through qualitative interviews with older prisoners prior to and following discharge from prison. Descriptive statistics were produced for all quantitative data, and qualitative data were analysed using the constant comparison method. Results: The number of older prisoner leads has increased in recent years but they do not all appear always to be active in their roles, nor in receipt of specialist training. Nearly half (44%) of establishments do not have an older prisoner policy. There is a lack of integration between health and social care services because of ambiguity regarding responsibility for older prisoners' social care. The responsible social service may be located a considerable distance from where the prisoner is held; in such instances, local social services do not co-ordinate their care. The most frequent unmet need on prison entry was the provision of information about care and treatment. Release planning for older prisoners was frequently non-existent. Limitations: The study used a cut-off age of 60 years as the lower limit for the definition of an older prisoner; evidence has emerged that supports a redefinition of that cut-off to 50 years. Our study examined the care provided for men and this should be considered if contemplating using the OSHCAP with older women in prison. Conclusion: The Older prisoner Health and Social Care Assessment and Plan (OHSCAP), developed as part of this study, provided a feasible and acceptable means of identifying and systematically addressing older prisoners' health and social care needs. Future work will include the conduct of a randomised controlled trial to examine the impact of the OHSCAP in terms of improving a range of outcomes, including economic impact. Funding: The National Institute for Health Research Health Services and Delivery Research programme.